Export destinations for Indian ornamental fish: Constant market share analysis* - RANI, PRATHVI; IMMANUEL, SHEELA (The Indian Journal of Animal Sciences, 2015)
Ornamental fish culture has emerged as a highly profit oriented lucrative sector. It is so called the million dollar industry. While most of the countries in the world have taken up the lead in ornamental fish trade, India is still a sleeping giant with a share of less that 1%. India has huge potential to develop this sector due to its rich resources of pisci flora and fauna. In the present study an attempt was made to study and examine the competitiveness of Indian ornamental fish exports amongst its important export destinations (Singapore, USA, Japan, Malaysia,Germany) using constant market share analysis. This study is based on the data pertaining from 1991-2009 from UNCTAD and WTO statistical data base. Constant market share gives an idea about whether the product exported has its own competitive nature or is competitiveness driven by the growth in world exports or demand of the product due to development in the destination market. CMS analysis suggested that India’s ornamental fish exports are more competitive in USA rather than other major export destinations like Singapore, Malaysia etc. India’s increase in export of ornamental fish to Singapore, Malaysia is mainly market driven rather than its own competitiveness. Therefore to sustain and enhance India’s competitiveness, India needs to have manifold increase in ornamental fish production, grow parallel with world’s trend in ornamental fish trade and export more to those countries where it is highly competitive in its own way.